National and International Regulations Regarding Shelf Life of Food Products - M Arpah; Rizal Syarief; Joko Hermanianto; Anton Apriyantono (Jurnal Teknologi dan Industri Pangan, 2003)
This paper discusses legal aspects of open dating system of food products in Indonesia, European Union and USA. The Codex Alimentarius Commision (CAC) regulation of the open dating system i.e. mandatory labelling of prepacked foods as stated in codex general standard for the labelling of prepacked foods is also highlighted. The regulations vary on a statutory authority basis from voluntary dating of all prepacked foods to mandatory open dating legislations. Since 1999, however, the presence or absence of a date has legal implications under Indonesian statutory authority. Key words: Kadaluwarsa, voluntary, mandatory.